Online Learning Management Using Google Sites on Relations and Functions in Pandemic Conditions - Robiul Khasanah; Siti Miftahul Muflihah (Journal of Education and Learning Mathematics Research (JELMaR), 2021)
The purpose of this study aims to describe learning management using google sites on relation and funcitions in pandemic at SMP Muhammadiyah 4 Singosari. This research uses descriptive qualitataive rearch methods. The data collection methods used in this study were interview, observation and documentations during the learning process. The subject of this study were students of class VIII SMP Muhammadiyah 4 Singosari. online learning learning management during pandemic conditions which includes planning, organizing, implementing, and monitoring. Online learning will be carried out with the help of google sites as a medium for delivering material. The planning stage includes observation, preparation of lesson plans, collection of material sources and preparation of learning media using google sites. The organizing stage includes determining the communication channels used for the online learning process and focusing resources towards the target. The implementation stage is the interaction carried out by teachers and students during learning. The supervision stage includes the evaluation stage in learning. Learning evaluation is carried out through student attendance and student activeness in participating in learning. student attendance recap shows an increase in each meeting. The use of google sites as a learning medium during the pandemic can be further developed to increase student motivation and make it easier for students to learn while carrying out online learning.